Substituição do milho pela glicerina em dietas de alto desempenho para bovinos de corte - Giotto, Francine Mezzomo (2015)
This research was conducted in order to evaluate the effects of glycerin levels inclusion in high performance diets for feedlot beef cattle on apparent digestibility of nutrients, dry matter intake, daily gain, feed efficiency and hot carcass yield. Thirty-two Brangus bulls were used, with initial body weight of 380 ± 20 kg, in a completely randomized design. Animals were housed in individual pens and subjected to 21 days of diets and facilities adaptation, followed by five experimental periods of 21 days each. The experimental diets were formulated so that the corn was replaced by glycerin at 0, 70, 140 and 210 g kg-1 levels, in the dry matter of total diet. Inclusion of glycerin in the diets up to 210 g kg-1 did not influence (P>0.05) apparent digestibility of dry matter (738.1 g kg-1), organic matter (747 g kg-1), crude protein (755.1 g kg-1), neutral detergent fiber (580.2 g kg-1) and total digestible nutrients (707.2 g kg-1). Glycerin inclusion in the diets did not influence (P>0.05) total dry matter intake (10.667 kg dia-1). Still, feed efficiency (0.133 kg kg-1), average daily gain (1.42 kg) and hot carcass yield (543.7 kg kg-1) have not been influenced by the glycerin (P>0.05). Glycerin can replace up to 1/3 of the corn and compose up to 21% of the diet for confined beef cattle with high gain rate, without changing apparent digestibility of nutrients, dry feed intake, daily gain, feed efficiency and hot carcass yield.